SMARCB1-deficient sinonasal adenocarcinoma: a rare variant of SWI/SNF-deficient malignancy often misclassified as high-grade non-intestinal-type sinonasal adenocarcinoma or myoepithelial carcinoma - Skálová, Alena; Taheri, Touraj; Bradová, Martina; Vaněček, Tomáš; Franchi, Alessandro; Slouka, David; Kostlivý, Tomáš; de Rezende, Gisele; Michálek, Jaroslav; Klubíčková, Natálie; Ptáková, Nicola; Nemcová, Antónia; et al. (Virchows Archiv : an international journal of pathology, 2024)
SMARCB1-deficient sinonasal adenocarcinoma is a rare variant of SWI/SNF-deficient malignancies with SMARCB1 loss and adenocarcinoma features. More than 200 high-grade epithelial sinonasal malignancies were retrieved. A total of 14 cases exhibited complete SMARCB1 (INI1) loss and glandular differentiation. SMARCA2 and SMARCA4 were normal, except for one case with a loss of SMARCA2. Next-generation sequencing (NGS) and/or fluorescence in situ hybridization (FISH) revealed an alteration in the SMARCB1 gene in 9/13 cases, while 2/13 were negative. Two tumors harbored SMARCB1 mutations in c.157C > T p.(Arg53Ter) and c.842G > A p.(Trp281Ter). One harbored ARID1B mutations in c.1469G > A p.(Trp490Ter) and MGA c.3724C > T p.(Arg1242Ter). Seven tumors had a SMARCB1 deletion. One carried an ESR1 mutation in c.644-2A > T, and another carried a POLE mutation in c.352_374del p.(Ser118GlyfsTer78). One case had a PAX3 mutation in c.44del p.(Gly15AlafsTer95). Histomorphology of SMARCB1-deficient adenocarcinoma was oncocytoid/rhabdoid and glandular, solid, or trabecular in 9/14 cases. Two had basaloid/blue cytoplasm and one showed focal signet ring cells. Yolk sac tumor-like differentiation with Schiller-Duval-like bodies was seen in 6/14 cases, with 2 cases showing exclusively reticular-microcystic yolk sac pattern. Follow-up of a maximum of 26 months (median 10 months) was available for 8/14 patients. Distant metastasis to the lung, liver, mediastinum, bone, and/or retroperitoneum was seen in 4/8 cases. Locoregional failure was seen in 75% of patients, with 6/8 local recurrences and 3 cervical lymph node metastases. At the last follow-up, 5 of 8 (62%) patients had died of their disease 2 to 20 months after diagnosis (median 8.2 months), and 3 were alive with the disease. The original diagnosis was usually high-grade non-intestinal-type adenocarcinoma or high-grade myoepithelial carcinoma. A correct diagnosis of these aggressive tumors could lead to improved targeted therapies with potentially better overall disease-specific survival.
Keywords: nádorové biomarkery; DNA vazebné proteiny; Mutation; senioři nad 80 let; Biomarkers, Tumor; gen SMARCB1; Adenocarcinoma; myoepiteliální nádor; senioři; lidé; Humans; lidé středního věku; nádory vedlejších dutin nosních; SMARCB1 Protein; Middle Aged; Aged, 80 and over; transkripční faktory; Female; Male; Diagnosis, Differential; Adult; Myoepithelioma; mutace; vysoce účinné nukleotidové sekvenování; stupeň nádoru; Paranasal Sinus Neoplasms; mužské pohlaví; Aged; Neoplasm Grading; DNA-Binding Proteins; adenokarcinom; ženské pohlaví; dospělí; High-Throughput Nucleotide Sequencing; Transcription Factors; diferenciální diagnóza; In Situ Hybridization, Fluorescence; hybridizace in situ fluorescenční